2011
DOI: 10.1038/gene.2011.50
|View full text |Cite
|
Sign up to set email alerts
|

A novel immunodeficiency disorder characterized by genetic amplification of interleukin 25

Abstract: Many primary immunodeficiency disorders of differing etiologies have been well characterized, and much understanding of immunological processes has been gained by investigating the mechanisms of disease. Here, we have used a wholegenome approach, employing single-nucleotide polymorphism and gene expression microarrays, to provide insight into the molecular etiology of a novel immunodeficiency disorder. Using DNA copy number profiling, we define a hyperploid region on 14q11.2 in the immunodeficiency case associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Such LCSH areas are likely to reflect the origin of recessive diseases, such as imprinting disorders, triploidy and duplications in which the pathogenic mutations are located (4). Although not observed in this study, 22q11 microdeletion syndrome (4) and IL-25 hyperdiploidy can be discovered by CNV analysis (15). SNVs related to inflammatory and autoimmune complications in common variable immunodeficiency (CVID) were reported (16).…”
Section: Discussionmentioning
confidence: 60%
“…Such LCSH areas are likely to reflect the origin of recessive diseases, such as imprinting disorders, triploidy and duplications in which the pathogenic mutations are located (4). Although not observed in this study, 22q11 microdeletion syndrome (4) and IL-25 hyperdiploidy can be discovered by CNV analysis (15). SNVs related to inflammatory and autoimmune complications in common variable immunodeficiency (CVID) were reported (16).…”
Section: Discussionmentioning
confidence: 60%
“…We previously investigated a functional molecular cause for this undiagnosed immunodeficiency through whole genome arrays. Briefly, analysis of Affymetrix 250K SNP microarray data of the case and a matched healthy control subject via a copy number analysis tool identified hyperploidy of a region centromeric to chromosome 14q11.2, mapped over the interleukin 25 ( IL25 ) gene ( 10 ). IL-25 (a member of the IL-17 family of cytokines) induction in mice has been previously associated with a T-helper (Th) 2-like pathological immune response ( 11 ) and shown to regulate the development of autoimmune inflammation mediated by IL-17-producing cells ( 12 , 13 ) and was deemed a plausible candidate for further analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Green et al ( 10 ) paired genetic analysis with transcriptional profiling and found a large number of genes associated with Th1/Th2 profiles to be differentially expressed in peripheral blood lymphocytes of the proband, indicative of a Th2 bias confirmed by flow cytometric analysis. T-cells from the proband and control subject were cultured and activated in vitro with qPCR analysis demonstrating higher IL25 expression in the proband when compared to the control.…”
Section: Introductionmentioning
confidence: 99%
“…IL17RB encodes a cytokine receptor that specifically binds to IL‐25 (IL‐17E) and IL‐17B, in which IL‐17B is thought to be an antagonist of IL‐25 binding ( 32 ). IL‐25 induces Th2‐type cytokine production in IL17RB‐positive cells ( 32 ), and in a case report, genetic amplification of IL‐25 led to an overactive Th2 response with a phenotype of recurrent varicella ( 42 ). In this analysis, the IL17RB locus variant was also associated with lowered proportions of Th17/Treg cells in healthy Japanese individuals.…”
Section: Discussionmentioning
confidence: 99%